Breast cancer survival rates and determinants in Ethiopia: a systematic review and meta-analysis of longitudinal studies - Abenezer Melaku Tafese; Meseker Tesfaye Fentie; Beminate Lemma Seifu; Angwach Abrham Asnake; Bikiltu Dugassa Dirbaba; Abdisa Gemedi Jara; Elsabeth Tizazu Asare; Brandon George (BMC Cancer)
Abstract Background Breast cancer is the most common cancer and the leading cause of cancer mortality among women in Ethiopia, accounting for 32% of new cancer cases and 17.6% of cancer deaths. Despite its growing burden, comprehensive data on survival rates and contributing factors remain limited. This systematic review and meta-analysis aimed to synthesize existing data on breast cancer survival in Ethiopia and identify key determinants influencing outcomes. Methods A comprehensive systematic search was conducted in PubMed, Web of Science, Scopus, Embase, and CINAHL to identify studies on breast cancer survival in Ethiopia published between January 2014 and August 2024. Eligible studies were screened and assessed for quality. A random-effects model was used to estimate pooled 1-, 3-, and 5-year survival rates and examine factors associated with survival. Results This review included 15 cohort studies with 6,232 breast cancer patients. The reported median age of patients ranged from 39.0 to 61.0 years, with median survival times varying between 10.0 and 58.7 months. Pooled 1-, 3-, and 5-year survival rates were 92.0% (95% CI: 85.0, 97.0), 66.0% (95% CI: 52.0, 78.0), and 22.0% (95% CI: 8.0, 40.0), respectively. Rural residence (AHR = 1.58, 95% CI: 1.15, 2.17), advanced-stage diagnosis (AHR = 2.56, 95% CI: 1.86, 3.52), and presence of comorbidity (AHR = 1.54, 95%CI: 1.20, 1.98) were associated with higher mortality, while initiation of hormonal therapy (AHR = 0.43, 95% CI: 0.30, 0.61) was associated with improved survival. Conclusion While short-term survival among breast cancer patients in Ethiopia is favorable, the 5-year survival rate remains significantly lower than regional and global estimates. Strengthening health system capacity and enhancing public awareness are critical to promoting early detection, ensuring timely treatment, and improving long-term outcomes. Protocol registration PROSPERO (CRD42024574529).